ANALISIS AKRILAMIDA PADA KRIPIK DAN KUDAPAN GORENG DARI UMBI-UMBIAN - Siti Aminah; Joko Teguh Isworo (Universitas Muhammadiyah Semarang, 2010)
Potential high acrylamide formation in food starch source prepared with pan frying. This study aims to: measuring and describing levels of acrylamide in snacks and chips from tubers. Diskriptif research designed to test 2 times. Materials used include: “talas”, potato, cassava and sweet potatoes, cooking oil, the standard acrylamide and other reagents. Tubers made snacks and chips, each performed with a frying pan and processing pengovenan. Acrylamide analysis performed by the method of High Performance Liquid Chromatography (HPLC) (Simanjuntak et al., 2004,). Diskriptif analyzed data with the help of SPSS version 15 and presented diskriptif. The results of analysis on acrylamide levels in the “timus” snack highest good sweet potato fries or oven, respectively 65, 244 mcg / g ± 2, 192; 65.425 mcg / g ± 2, 268, lowest in both fried potato croquettes or oven, each of each was 42.590 mcg / g ± 0.000; 43, 012 mcg / g ± 0, 074. Similarly, the highest in the chips are potato chips, fried and oven whether each for 111, 391 mcg / g and 0000 ± 99, 895 mcg / g ± 4702, whereas the lowest levels are in fried potato chips as many as 13,023 mcg / g ± 0000. To do further research about the effects of long storage of materials tubers after harvest and non enzimatis Browning reactions during the processing of acrylamide formation and the influence of early treatment on the tubers before processing to minimize the formation of acrylamide.